Development of a portable type i to III lightning surge protective device for compact structures - Gomes A.; Ab Kadir M.Z.A.; Gomes C.; Khurshid Z.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Building wiring; Continuous time systems; Hardware; Lightning; Lightning protection; Railroad transportation; Railroads; Vehicle transmissions; Base transmission stations; Compact structures; Hardware implementations; Large structures; Lightning surges; Market researches; Surge protective devices; Transient voltage; Surge protection